Impact and implementation of UNESCO's Recommendation on Open Educational Resources in academic libraries: SPARC Europe Case Study - Gema Santos-Hermosa (Association for Learning Technology, 2024)
This paper analyses the role of libraries in the development of Open Educational Resources (OER) and, more specifically, the impact and level of implementation of UNESCO's (2019) OER Recommendation in Higher Education libraries. This study, the result of a joint undertaking between a national R&D project and SPARC Europe, is based on an online survey, disseminated amongst the European Network of Open Education Librarians (ENOEL) and uses a descriptive research methodology. The results highlight the implementation actions being taken by university libraries (n = 136) in each of the five areas of action of UNESCO's Recommendation. We find that the main contributions are being made in the areas of capacity building and Open Education policies, but that considerable work has yet to be done in terms of promoting inclusiveness and the sustainability of OER. Thus, the full implementation of UNESCO's recommendation requires a greater commitment on the part of librarians to joint actions undertaken via international networks and projects, as well as greater institutional commitment and the building of interdepartmental alliances.